2016
DOI: 10.1021/acs.biochem.5b01339
|View full text |Cite
|
Sign up to set email alerts
|

Strict Regiospecificity of Human Epithelial 15-Lipoxygenase-2 Delineates Its Transcellular Synthesis Potential

Abstract: Lipoxins are an important class of lipid mediators that induce the resolution of inflammation and arise from transcellular exchange of arachidonic acid (AA)-derived lipoxygenase products. Human epithelial 15-lipoxygenase-2 (h15-LOX-2), the major lipoxygenase in macrophages, has exhibited strict regiospecificity, catalyzing only the hydroperoxidation of carbon 15 of AA. To determine the catalytic potential of h15-LOX-2 in transcellular synthesis events, we reacted it with the three lipoxygenase-derived monohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 67 publications
8
29
0
Order By: Relevance
“…Measurements of kinetic characteristics of AA-PE oxidation vs free AA oxidation by 15LO1 and 15LO2 in the presence and absence of human PEBP1 for both enzymes, showed that the action of PEBP1 was unidirectional although the effects were more robust for 15LO2 than 15LO1 (Table S1). Vmax, Km, Kcat and Kcat/Km for free AA as a substrate in the absence of PEBP1 were in reasonable agreement with the previously published data for 15LO2 (Green et al, 2016). When PEBP1 was added to 15LO2, we found no significant changes in Vmax, a 1.7-fold increase in Km and a slight decrease of Kcat/Km for free AA.…”
Section: Resultssupporting
confidence: 91%
“…Measurements of kinetic characteristics of AA-PE oxidation vs free AA oxidation by 15LO1 and 15LO2 in the presence and absence of human PEBP1 for both enzymes, showed that the action of PEBP1 was unidirectional although the effects were more robust for 15LO2 than 15LO1 (Table S1). Vmax, Km, Kcat and Kcat/Km for free AA as a substrate in the absence of PEBP1 were in reasonable agreement with the previously published data for 15LO2 (Green et al, 2016). When PEBP1 was added to 15LO2, we found no significant changes in Vmax, a 1.7-fold increase in Km and a slight decrease of Kcat/Km for free AA.…”
Section: Resultssupporting
confidence: 91%
“…These values indicate that DHA has the fastest rate of substrate capture at low substrate concentrations, kcat/KM, but 7S-HDHA has the fastest rate of product release at high substrate concentrations, kcat (49). For comparison, the kinetic parameters for h15-LOX-2 and AA are 0.96 sec -1 for kcat and 0.19 sec -1 µM -1 for kcat/KM, similar to published values (15,43), indicating that at low substrate concentration, 7S-HDHA is a comparable substrate to that of AA, but DHA is preferred. These data support Pathway 5 (Scheme 1) as the most likely in vitro biosynthetic route for RvD5 production.…”
Section: Reaction Of 7s-hdha and 7s-hpdha With H15-lox-2 In Biosynthesupporting
confidence: 85%
“…Previously, it was shown that h15-LOX-2 oxygenated 5S-HpETE, but not 12S-HpETE or 15S-HpETE (15). Together with the current work, this suggests that the h15-LOX-2 active site tolerates substrates which are oxygenated close to the carboxylate end, but not those substrates oxygenated closer to the methyl end.…”
Section: Biosynthesis Of 7s17s-dihdha (Rvd5)supporting
confidence: 81%
See 2 more Smart Citations